STRATEGIES IN THE TRANSLATION OF FIGURATIVE LANGUAGE IN BRUNO MARS’ SELECTED SONGS - Hesti Jayanti; Evert Hilman; Evi Jovita Putri (IKIP Siliwangi, 2022)
Translating figurative language especially in a song lyric is not easy, therefore, it uses translation strategies to translate song lyrics it becomes an important part of the song lyric to strengthen the message and creativity of the lyric itself. This study is aimed to analyze the translation strategies of figurative language in lyric songs and to find out the strategies in the lyric songs translated. The lyrics are selected from 3 albums of Bruno Mars, namely: Doo-Whoops & Hooligans album, 24k Magic album, and Unorthdox Jukebox album. This study uses a descriptive qualitative method. This study uses strategies translation by Chesterman’s theory which only focuses on syntactic and semantic strategies, while Searle’s theory is applied to identify the classification of speech act. This study demonstrates how to scheme change, transposition, unit shift and literal translation are used as the syntactic strategies, while trope change, distribution change and synonymy are applied for semantic strategies. In addition, there are three types of speech acts found in the data, they are assertive, declarative and expressive. Based on the result, Scheme Change is the most common syntactic strategy and Trope Change is the most common semantic strategy, while the assertive is the most dominant type of speech act. Keywords: Translation Strategies, Figurative Language, Speech acts, Song Lyric